50 years of teaching introductory economics. Issue 3 (3rd July 2019) - Hamermesh, Daniel S.
Abstract: The author of this article describes his experiences in teaching huge classes of principles of economics over the last half-century. He lays out changes in pedagogy and illustrates various novel devices used to explain economic ideas and hold students' attention. Additionally, he considers the appropriate sizes of intro classes and weighs the advantages and disadvantages of alternative methods of staffing them.